STUDY OF THE STABILITY OF THE REGULATOR BALANCING ROBOT NI MINDSTORMS - Wojcik Waldemar; S.A.Kulmamirov; Zh.M.Alimzhanova; L.M. Alimzhanova; A.M. Akhmetova; V.I. Karyukin (Academic Scientific Journal of Computer Science, 2019)
The article presents the results of studying the steady state of a balancing robot when the control is carried out in a closed state. The synthesis of the controller’s coefficients was carried out by estimating the root of the characteristic equation and the linear quadratic regulator. Under the action of the PID controller, algorithms for controlling the robot servos were compiled. The results of the experimental studies allowed us to construct transient characteristics in a closed robot control system while balancing the state of the robot in a steady state and in motion.